(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic influenced the behavior patterns of the Brazilian population, especially with regard to health care. The unguided use of home medication, supplements, herbs and allopathic medicine spread mainly through the internet, social network and message apps has caused an increase in demand for these products in order to prevent or treat clinical outcomes caused by the new coronavirus. So, the objective of this study was to verify changes in the consumption of popular known items in the treatment of the flu syndromes and to identify the sources most used by participants to seek information about the pandemic as well as therapeutic guidelines to treat COVID-19. Using a descriptive exploratory methodology, this study has collected data through an online questionnaire for the Bahia population with 323 participants. The results showed that there was a significant increase in the consumption of some vitamins and supplements (average of 22%), herbs and foods (average of 58%) and drugs (average of 15%). The internet was the main source of information about the pandemic (86.3%), however 95% of the participants said that health professionals were trained to recommend appropriate therapies for COVID-19. Therefore, the rational and guided use of any supplements, medicines and homemade formulations must be imperative in the face of any disease, such as COVID-19 despite of the benefits propagated by popular knowledge of inadequate self-supplementation and use of medicine without proper care, proven safety and efficacy can cause adverse reactions or even irreversible damage to health.